Released Myeloperoxidase Attenuates Neutrophil Migration and Accumulation in Inflamed Tissue - Rehring, Jacob F.; Bui, Triet M.; Galán-Enríquez, Carlos Samuel; Urbanczyk, Jessica M.; Ren, Xingsheng; Wiesolek, Hannah L.; Sullivan, David P.; Sumagin, Ronen (Frontiers in Immunology, 2021)
Neutrophil (PMN) recruitment to sites of insult is critical for host defense, however excessive PMN activity and tissue accumulation can lead to exacerbated inflammation and injury. Myeloperoxidase (MPO) is a PMN azurophilic granule enzyme, which together with H2O2, forms a powerful antimicrobial system designed to kill ingested bacteria. Intriguingly, in addition to intracellular killing of invading microorganisms and extracellular tissue damage due generation of ROS, soluble MPO has been directly implicated in modulating cellular responses and tissue homeostasis. In the current work, we used several models of inflammation, murine and human PMNs and state-of-the-art intravital microscopy to examine the effect of MPO on PMN migration and tissue accumulation. We found that in the absence of functional MPO (MPO knockout, KO mice,) inflammatory PMN tissue accumulation was significantly enhanced. We determined that the elevated numbers of PMNs in MPO knockout mice was not due to enhanced viability, but due to increased migratory ability. Acute PMN migration in models of zymosan-induced peritonitis or ligated intestinal loops induced by intraluminal administration of PMN-chemokine CXCL1 was increased over 2-fold in MPO KO compared to wild type (WT) mice. Using real-time, intravital imaging of inflamed mouse cremaster muscle and ex vivo PMN co-culture with inflamed endothelial cells (ECs) we demonstrate that elevated migration of MPO KO mice was due to enhanced adhesive interactions. In contrast, addition of soluble recombinant MPO both in vivo and ex vivo, diminished PMN adhesion and migration. Although MPO has been previously suggested to bind CD11b, we found no significant difference in CD11b expression in either resting or activated PMNs and further showed that the MPO binding to the PMN surface is not specific to CD11b. As such, our data identify MPO as a novel regulator of PMN trafficking with potential implications for inflammation resolution and wound healing.